Magnetic Susceptibility Applied To Sinter Characterization: Preliminary Study - Érica Simões Rodrigues; Ramiro da Conceição do Nascimento Júnior; Marcos Tadeu D’Azeredo Orlando; João Batista Ribeiro Martins (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
In order to guarantee the quality of the sinter and process control some measurements are made such as RDI and FeO (Fe2+). However, the behavior of sinter during reduction in the blast furnace is not always understood, when it is analyzed only metallurgical, physical and chemical quality. Therefore, it is necessary to find alternative techniques to understand more this behavior. In this work four experimental trials were performed to obtain sinter samples with different FeO (Fe2+) contents. Optical microscopy was performed to identify and quantify the phases in sinter and to evaluate the magnetic behavior of each one, the Magnetic Susceptibility technique was used. The results obtained between Optical Microscopy, Magnetic Susceptibility and quality parameters were compared and then was identified that Magnetic Susceptibility may be an alternative to help the understanding of sinter behavior in Blast Furnace.